(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Some morphological and biological charactecistics of several species of Agromyzidae are illustrated; Hexomyza schineri (Giraud), Agromyza albitarsis Meigen, Japanagromyza salicifolii (Collin) and Phytomyza mayeri (Spencer) are recorded for the first time from Italy; the presence of Agromyza cinerascens (Macquart), Liriomyza bryoniae (Kaltenbach), Liriomyza eupatorii Kaltenbach and Liriomyza congesta Becker in Italy is confirmed and new distributional data are given and the status of Phytomyza mayeri (Spencer) is changed.